Residual effect of sunflower (Helianthus annuus) stover and P management and direct effect of N and P on productivity, nutrient uptake and economics of spring sunflower - BABU, SUBHASH; RANA, D S; YADAV, G S; ANSARI, M A (The Indian Journal of Agricultural Sciences, 2013)
A fixed plot field experiment was carried out during kharif and spring seasons of 2008-09 and 2009-10 at New Delhi, to study the residual effect of sunflower (Helianthus annuus L.) stover and P management and direct effect of N and P on productivity, nutrient uptake and economics of spring sunflower. Residual effects of sunflower stover incorporation and 30 kg P/ha and direct effect of recommended dose (RD) of NP (80 kg N + 15 kg P/ha) resulted in higher yield attributes, seed, stover and biological yields, gross returns, net returns, B:C ratio and uptake of N, P and K. Residual effect of sunflower stover incorporation increased seed yield of sunflower by 14.9 and 25.9% over the no stover incorporation during 2009 and 2010, respectively. Residual effect of 30 kg P/ha caused 22.3% and 24.4% increase in the seed yield of sunflower over the control during 2009 and 2010, respectively. Direct effect of RD of N and P (80 kg N + 15 kg P/ha) recorded the maximum seed yield (2.85 and 2.57 tonnes/ha) during both the years, which was significantly higher than 50% RD of NP (2.56 and 2.27 tonnes/ha) and control (1.70 and 1.57 tonnes/ha). Increase in seed yield due to RD of NP was 11.3 and 13.2% higher than 50% RD of NP and 67.6 and 63.7% than control. With regards to economics and nutrients uptake, residual effect of sunflower stover incorporation and 30 kg P/ha recorded significantly higher values of gross returns, net returns and B: C ratio and NPK uptake over control (no stover incorporation) and other P levels, respectively. Among the different doses of NP applied to sunflower, direct effect of RD of NP (80 kg N + 15 kg P/ha) registered the highest gross returns (64.11 × 103 and 6.13 × 103 Rupees/ha), net returns (48.76 × 103 and 44.66 × 103 Rupees/ha) and B:C ratio (3.19 and 2.80).